Estudo do óleo das sementes de Carthamus tinctorius L. Para produção de biodiesel - Morais, Ellen Kadja Lima de (2012)
Most of the energy consumed worldwide comes from oil, coal and natural gas. These sources are limited and estimated to be exhausted in the future, therefore, the search for alternative sources of energy is paramount. Currently, there is considerable interest in making trade sustainable biodiesel, a fuel alternative to fossil fuels, due to its renewable nature and environmental benefits of its use in large scale. This trend has led the Brazilian government to establish a program (Probiodiesel) with the aim of introducing biodiesel into the national energy matrix, by addition of 5% biodiesel to conventional diesel in 2010 to foster not only the increase of renewable energy, but reduce imports of crude oil. This work evaluates different methods of extraction of oil Carthamus tinctorius L., their characterization by IR, 1H and 13C NMR, HPLC and TG and their use in the production of methyl ester (molar ratio of oil / alcohol 1:6, and NaOH catalyst). The physico-chemical parameters (acid value, density, viscosity, saponification index and surface tension) of oil and biodiesel were also described. The produced biodiesel had a yield of 93.65%, was characterized in relation to their physicochemical properties showing satisfactory results (density=875 kg/m3, viscosity = 6.22 mm2/s, AI = 0.01 mg (NaOH) /g) compared with the values established by the the National Agency Oil, Natural Gas and Biofuels